PENGARUH BRIEF COUNSELING FARMASIS TERHADAP AKTIVITAS FISIK DAN HASIL TERAPI PASIEN HIPERTENSI RAWAT JALAN DI POLIKLINIK PENYAKIT DALAM RSUD ULIN BANJARMASIN - Saftia Aryzki; Noverda Ayuchecaria; Anna Khumaira Sari (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2019)
According to Riskesdas (2013) the prevalence of hypertension in South Kalimantan Province is 30.4%, this means around 1,145,536 people. Risk factors are occupation of less physical activity 26.1% and residents> 10 years consuming less vegetables and fruits. The government invites the entire community to carry out a movement of healthy living people by doing physical activities, consuming vegetables and fruits and checking health regularly. The purpose of this study was to determine the effect of Brief Counseling of Pharmacists on Physical Activity and Therapeutic Results of Hypertensive Patients Outpatient in the Internal Medicine Polyclinic of Ulin Hospital, Banjarmasin.The quasi-experimental study used a prospective two-group pretest and posttest design. Patients were grouped randomly into two groups, namely the group that received the intervention in the form of a pharmacist / researcher briefing and group without intervention (control) followed for one month. Sampling using co-executive sampling method that meets the inclusion and exclusion criteria. The study was conducted at the internal medicine clinic at Ulin Banjarmasin Public Hospital in the period January-March 2018. The instrument used is International Physical Activity Questionnaire (IPAQ).The results of physical activity data analysis in the control group with the Wilcoxon Test which showed data had a significant difference (p <0.05), while in the treatment group with the Wilcoxon Test which showed data did not have a significant difference (p> 0.05). Analysis of blood pressure data in the control group with the Wilcoxon Test which showed data had a significant difference (p <0.05), while in the treatment group with the Wilcoxon Test which showed data had a significant difference (p <0.05).